The Influence of Leadership on the Performance of State Civil Services through Work Motivation and Satisfaction - Khairunnisa Khairunnisa; Yunus Amar; Abdullah Sanusi (Hasanuddin Journal of Business Strategy, 2021)
This study aims to determine the effect of leadership on employee performance through work motivation and job satisfaction at the Secretariat of the Takalar Region Representative Council. Data collection was carried out at the Secretariat of the Takalar Region Representative Council. The study applies saturated samples so that the number of samples was 49 respondents. Data were analyzed using the path analysis method. The results showed that leadership has a positive and significant effect on work motivation and job satisfaction, but an insignificant effect on employee performance. Work motivation has a positive and significant effect on employee performance; Job satisfaction has a positive and significant effect on employee performance. Leadership through both work motivation and job satisfaction show a significant effect on employee performance.